Integrating poverty, gender and environmental concerns into value chain analysis: A conceptual framework and lessons for action research - Simon Bolwig; Stefano Ponte; Andries du Toit; Lone Riisgaard; Niels Halberg (Danish Institute for International Studies (DIIS), 2008)
Many contemporary development solutions and policy prescriptions place emphasis on the potential for closer integration of poor people or areas with global markets. But the prospects for the reduct-ion of chronic poverty depend in great measure on the nature of the broader economic processes that, according to how they are configured, can either exacerbate or alleviate poverty. These pro-spects also depend on the forms of local economic growth that impact on the lives of the poor. Since the mid 1990s, a literature has emerged on value chains that has helped increase our understanding of how firms and farms in developing countries are integrated in global markets. Studies using the global value chain approach examine different types of value chain governance and the opportunities they provide for technological or functional upgrading of traders and producers in developing countries. But few value chain studies have succeeded in explicitly documenting the impact of value chain activities on poverty, gender and the environment. In this light, the paper develops a conceptual framework that can help overcome the shortcomings highlighted so far in 'stand-alone' value chain, livelihoods and environmental analyses by integrating the 'vertical' and 'horizontal' aspects of value chains that affect poverty and sustainability. This framework is used to draw lessons for external interventions in value chains targeted at small pro-ducers and other weak actors in developing countries, particularly the kinds of interventions known as 'action research' which puts emphasis on strategic and political approaches to achieving sustained improvements for disadvantaged groups. A companion paper to the present one develops a strategic framework and practical methods to guide action research in value chains (Riisgaard et al., 2008). The entire methodology will be tested during 2008-09 by seven action research projects targeted at poor rural producers in Africa and Asia. All projects form part of the Rural Poverty and Environment programme of the International Development Research Centre and are carried out as part of the RPE research theme 'integrate poverty and environmental concerns into value chain analysis' under the guidance of the Overseas Development Institute, London.
Keywords: 330; Armutspolitik; Internationale Arbeitsteilung; Wirtschaftsintegration; Betriebliche Wertschöpfung; Umweltschutz; Gleichberechtigung; Entwicklungsländer